Economic impact of giving land to refugees - Mawejje, Joseph (Elsevier, 2024)
This paper adds to a sparse but growing literature on the economic costs and benefits of hosting refugees, including a unique policy of providing refugees with access to cultivable land. We construct a general equilibrium model from microsurvey data to simulate the spillover effects of giving land to refugees on income and production in the host-country economy surrounding a refugee settlement in Uganda. Reduced-form econometric analysis of land allocations at the refugee settlement, robust to several specifications, confirms the simulation finding that providing refugees with agricultural land significantly improves their welfare and self-reliance. Simulations reveal that refugee aid and land allocations generate positive income spillovers in the local economy out to a 15- km radius around the refugee settlement. Host-country households benefit significantly from the income spillovers that refugee assistance creates, and host-country agriculture is the largest beneficiary among production sectors.
Keywords: general equilibrium; immigration; land; refugees; spillovers; Uganda